眺望与俯瞰 ：中国现代文学中的南洋华人形象 = The studies of Nanyang Chinese depiction in modern China literature - 陈韦翰 Tan, Wee Han (2017)
纵观中国20世纪现代作家著作，「南洋华人」的形象建构成为这些作品再现南洋的衔接，而随着作者自身对南洋的考察取材，外加对南洋华人不同命题上的偏重，这一些作品的南洋华人形象便随着时代的递进而逐渐多元化。本文旨于采用文本解读的方式，通过考察不同中国现代作家作品中再现的南洋与南洋华人形象，对20世纪以降的中国文学中的南洋异域形象进行整合，并除了观察其中的规律性，也探讨其书写模式背后的推动与意义。本文主要研究的作品范畴围绕着三名中国现代文学中颇具代表性的作家——即徐志摩、老舍以及张爱玲，并且通过他们的著作，进一步了解这一代中国作家描写南洋风貌或南洋华人的不同层面与分类。If we were to observe modern literature works from China during the twentieth century, we would see a significant amount of depictions of Nanyang region and its representation of the Nanyang Chinese ethnic in those stories. Due to varying subject matters chosen by those authors, coupled with their prerequisite knowledge and observations of Nanyang, these constructed images diversified over the years. This thesis seeks to uncover the various forms of Nanyang Chinese depiction from the eyes of China author in the twentieth century. By studying the configuration of Nanyang Chinese in their work, the essay seeks to classify these representations, while exploring the motives and significance behind these theoretical premises by the Chinese authors. This thesis would be studying on three of the most influential writers in Chinese literatures, namely Hsü Chih-mo, Lao She and Eileen Chang, and their literature works to gain extensive views of Nanyang Chinese depiction in modern China literature.